METODOLOGICAL PRINCIPLES OF THE COMPETITIVE STRATEGIES FORMATION FOR HEALTH CARE ORGANIZATIONS - Тринчук, А.А.; Жарлінська, Р.Г.; Пилипчук, В.Л. (Modern engineering and innovative technologies, 2023)
The article is devoted to the methodological aspects of the competitive strategies formation of health care organizations (HCOs) - in particular, principles, methods, models, classification, mechanism, approaches and schemes. Modern approaches to understa